The rising influence of lipid metabolism in lung cancer: a global research perspective - Wang, Chaoqun; Lei, Ming; Wang, Wei; Jiang, Yuanyuan; Zhang, Jiefeng; Zhang, Yi; Zhao, Bin; Wang, Wenyang (Frontiers in Oncology, 2025)
BackgroundLung cancer is a prevalent malignant neoplasm globally and the leading cause of cancer-related mortality, posing a significant threat to human health and imposing a considerable societal burden. Researchers have recently focused more on lipid metabolism in lung cancer. However, to date, there has been no bibliometric analysis of lung cancer in relation to lipid metabolism. This study used bibliometric methods to analyze the link between lipid metabolism and lung cancer.MethodsPublications on lung cancer and lipid metabolism from 1995 to 2024 were sourced from the Web of Science Core Collection (WoSCC). The Microsoft Excel, R-bibliometrix, CiteSpace, and VOSviewer software were used to analyze and visualize the data.ResultsIn this study, a total of 535 publications were identified, with a marked increase in the number of publications observed post-2016. Both China and the United States exerted substantial influence in this domain. Notably, the Chinese Academy of Sciences and Huazhong University of Science and Technology have demonstrated leadership in various aspects of lipid metabolism research related to lung cancer. Professor Ana Ramirez de Molina and Frontiers in Oncology were the most productive authors and journals respectively. Besides, keywords like “lipid metabolism”, “lung cancer”, “expression”, “metabolism” and “growth” were central to current research and are expected to continue driving future trends in lung cancer and metabolism studies.ConclusionsResearch on the relationship between lung cancer and lipid metabolism was still in its early stages. Targeting lipid metabolism in lung cancer represented a promising therapeutic strategy, as inhibiting key enzymes involved in lipid biosynthesis and uptake has the potential to impede cancer progression and mitigate drug resistance. This bibliometric study was the first to thoroughly summarize research trends and developments in this area over the past thirty years, providing scholars with updated insights and identifying future research directions.